Faktor Penghambat Balai Besar Pelaksanaan Jalan Nasional Wilayah Sumbar (BPJN) dalam Melaksanakan Pengawasan Pembangunan Jalan di Kecamatan Sijunjung Kabupaten Sijunjung - Ake Fernandes; Hasbullah Malau (PUBLICNESS: Journal of Public Administration studies, 2022)
This study intends to find out the inhibiting factors for the Central Sumatran National Road Implementation Center in Implementing Road Construction Supervision in Sijunjung District, Sijunjung Regency. As for the various problems of supervising actions that are very poorly implemented because there are still many roads with holes, there are still many supervisory deviations such as the work of handling road asphalt in Sijunjung District, Sijunjung Regency so that the results look careless and the supervisory function of the Regional National Road Implementation Center (BPJN) is not optimal. sources such as paving are not perfect so there are cracks and peeling. This research was conducted with a qualitative type with a descriptive method, in determining the informants the researcher used purposive sampling methods and techniques. For data collection techniques, interviews, observations, and documentation were carried out. In testing the validity of the data, the researcher used a method triangulation technique. As for the data analysis technique using data reduction, data presentation, and conclusions. The results showed that the inhibiting factors for the Central Sumatra Regional National Road Implementation in Carrying out Supervision of Road Construction in Sijunjung District, Sijunjung Regency, were the lack of field supervisory personnel and the lack of supervision costs as well as facilities and infrastructure